Hijab Discourse in Indonesia: Unraveling the Narratives of Freedom, Religion, and Media Representation - Andina, Tri Kurnia Revul (CHANNEL: Jurnal Komunikasi, 2023)
This study delves into the intricate narratives surrounding the hijab in Indonesia, exploring the multifaceted perspectives presented by Deutsche Welle (DW) Indonesia, a transnational media entity. In the context of Indonesia, a nation characterized by religious diversity, the hijab has become a focal point of discussions, particularly concerning its compulsory nature and its implications for women's freedom and religious identity.  The study critically analyzes DW's portrayal of hijab-wearing Indonesian Muslim women, highlighting the interplay between media representations, cultural identities, and societal perceptions. Employing Sara Mills' critical discourse analysis, the research examines the subject-object positions within DW's coverage, unraveling the complexities of hijab discourse. Through the examination of DW Indonesia's coverage, the study reveals diverse perspectives, emphasizing the non-compulsory nature of hijab, the potential limitations it imposes on women, and the societal pressures associated with wearing it. However, the research underscores the need for a cautious interpretation of these narratives, recognizing the inherent complexities of individual choices, sociocultural backgrounds, and religious beliefs. The study also addresses the influence of global perceptions and Western biases, urging a critical approach to media representations. The research not only contributes to the scholarly discourse on media representations but also critically examines the intersection between religion, freedom, and media influence in contemporary Indonesian society.